The Successful Implementation of Education Management in STAISA - H. Asep Idrus Alaw (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
And its education management has a backbone.play a role in any school's performance and reputation. Schools use a variety of Strategies for maintaining higher educational quality than their competitors. In a similar myriad, The current study evaluated the success factors and variables that followed. STAISA for the effective application and practise of education management. system. The study had investigated Various aspects, including the curriculum, learning facility, and financing School infrastructure, connection, or communication from society, Education management instructors' quality, experience, training, and course offerings and qualification, among others. The study examined STAISA education management. The system employs a qualitative research approach and an interview tool for Data gathered from the administration authorities, including the principal. Vice-principal and other school decision-makers. Data Analysis The technique used was thematic analysis and thought mapping. The findings imply that.The school has been successful at Implemented a rigorous academic curriculum and connected departments. Putting emphasis on cooperation and communication among all stakeholders.